Massively Multiplayer Online Games and Well-Being: A Systematic Literature Review - Raith, Lisa; Bignill, Julie; Stavropoulos, Vasileios; Millear, Prudence; Allen, Andrew; Stallman, Helen M.; Mason, Jonathan; De Regt, Tamara; Wood, Andrew; Kannis-Dymand, Lee (Frontiers in Psychology, 2021)
Background: Massively multiplayer online games (MMOs) evolve online, whilst entailing large numbers of participants who play concurrently. Their online socialization component is a primary reason for their high popularity. Interestingly, the adverse effects of MMOs have attracted significant attention compared to their potential benefits. Methods: To address this deficit, employing PRISMA guidelines, this systematic review aimed to summarize empirical evidence regarding a range of interpersonal and intrapersonal MMO well-being outcomes for those older than 13. Results: Three databases identified 18 relevant English language studies, 13 quantitative, 4 qualitative and 1 mixed method published between January 2012 and August 2020. A narrative synthesis methodology was employed, whilst validated tools appraised risk of bias and study quality. Conclusions: A significant positive relationship between playing MMOs and social well-being was concluded, irrespective of one’s age and/or their casual or immersed gaming patterns. This finding should be considered in the light of the limited: a) game platforms investigated; b) well-being constructs identified; and c) research quality (i.e. modest). Nonetheless, conclusions are of relevance for game developers and health professionals, who should be cognizant of the significant MMOs-well-being association(s). Future research should focus on broadening the well-being constructs investigated, whilst enhancing the applied methodologies.